Advances in endoscopic visualization of colorectal polyps. - Yeung, T; Mortensen, N (2011)
AIM: Conventional white-light endoscopy is currently the gold standard for the detection and treatment of colorectal polyps. However, up to a fifth of polyps may be missed on initial examination, especially flat and small mucosal lesions. This study reviews the literature reporting on the use of new advances in endoscopic visualization. METHOD: Literature searches were performed on PubMed using the terms 'chromoendoscopy', 'narrow-band imaging' (NBI), 'autofluorescence imaging' (AFI), 'Fujinon Intelligent Colour Enhancement' (FICE), 'i-Scan colonoscopy', 'zoom colonoscopy' and 'confocal laser endomicroscopy' (CLE). We focused on systematic reviews, national guidelines and randomized controlled trials written in English. Studies were assessed for methodological quality using QUADAS. Prospective studies assessing new technology were also reviewed. Further publications were identified from reference lists. RESULTS: Chromoendoscopy increases the detection of neoplastic polyps compared with conventional colonoscopy. NBI avoids the use of additional dyes and enhances the vascular network of capillaries surrounding the crypts, increasing the adenoma detection rate and the ability to distinguish between neoplastic and non-neoplastic lesions. FICE, AFI and i-Scan are new developments that improve tissue contrast. Zoom endoscopy may be combined with different modalities to help further characterize colonic lesions. CLE provides live in vivo high-resolution optical sections of tissue and may be particularly useful in the surveillance of patients with long-standing ulcerative colitis, reducing the number of random biopsies. CONCLUSION: Although there is mounting evidence that these new technologies are superior to conventional endoscopy, current guidelines are limited. Further large-scale randomized controlled trials comparing these modalities in different patient subpopulations are warranted.